Association between pressure injury prediction and biochemical markers - Fernandes, Luciana Magnani; Silva, Letícia da; Oliveira, João Lucas Campos de; Souza, Verusca Soares de; Nicola, Anair Lazzari (Rev Rene, 2016)
Objective: to verify the association of pressure injury prediction with albumin, hematocrit and hemoglobin levels. Methods: documentary study, developed in an Intensive Care Unit for Adults with records of eligible patients (n=255). Sociodemographic and clinical characterizations lesion, development of pressure injury and region; a score of the Braden scale and results of biochemical markers were extracted. There was a descriptive and inferential statistical analysis, adopting a significance level of 5.0%. Results: there was a prevalence of males (64.7%) and surgical patients (69.8%). There was no significant association between hematocrit and hemoglobin markers with the pressure injury prediction, unlike albumin levels (p=0.023).Conclusion: there is an injury pressure prediction association in the albumin. The protein intake of the patient should be seen in greater detail by the health team.